Web-Gis Based School Zone Determination In Sungai Penuh City - Yuhanda, Ilham; Yulfa, Arie; Antomi, Yudi (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
When selecting the Acceptance of New Students (PPDB) for the zoning route, students have difficulty determining the school zone according to their place of residence. So far, the determination of school zones only uses google maps, but the application is not explicitly designed for it. Through WEB-GIS, problems related to school zoning can be solved because this application provides spatial information specifically in determining distances that can be used as WEB-GIS. The steps taken are to select the research location, conduct a system engineering analysis of the system, and design, and implementation of the trial use and operation of the system. In systems engineering, interviews, observations, and questionnaire surveys were conducted. This system engineering is intended to find out the proposal from system analysis as the basic design material after that it enters the application development. The final stage in developing the system is testing its use by the school and students and operating the system. The results obtained for system analysis must provide school zoning information facilities that can edit data, upload data, and delete data. The test results show that the system can be run more than 75% of the respondents said they were satisfied and very satisfied. Based on t